Advancing Swine Management in Buenavista, Guimaras: Foundations for Effective Extension Program - Vergara, Julius (Journal of Interdisciplinary Perspectives, 2024)
This research paper was created to assess the management practices of swine raisers in Buenavista, Guimaras. The health of livestock and the economic sustainability of the farming sector in Guimaras, Philippines, are contingent upon the management and disease prevention strategies employed in pig farming. This study employed a descriptive design utilizing quantitative methods to analyze data through frequency counts and percentages, assessing swine management techniques among fifty swine raisers in Buenavista, Guimaras. The sample comprised fifty swine producers, predominantly aged between 46 and 58. Women represented 54% of the respondents, with 60% indicating that their spouses predominantly managed pig farming activities. Moreover, 58% of interviewees indicated they lacked primary authority within their households. Seventy-four percent of participants commenced pig farming between 2012 and 2022, with the majority (ninety-two percent) possessing between one and forty pigs. Seventy-seven percent of farms provide triennial feeding for pigs, indicating a general consistency in feeding practices. Ninety-six percent of all option groups indicated a preference for grower feed and a rejection of swill feeding. Although they adhered to the standards for normal feeding, their sanitation practices were inconsistent; merely 52% reported cleaning pigpens thrice daily, and only 24% utilized disinfectants. A similar trend in recordkeeping was noted: just 64% of pig producers kept a journal of their operations. 84% of respondents indicated their swine efforts were adjacent to a pig-rearing farm.